Agenda Governamental: Influências na sua construção nos municípios integrantes da 31ª Secretaria de Desenvolvimento Regional de Itapiranga – SC - Ari Söthe (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2018)
The construction of government agendas with the participation of different actors precedes the planning of public policies. Thus, this article aims to describe the influence of different events, actors and issues in the construction of the agenda of the municipalities of the region covered by the 31th Department of Regional Development (DRD) of Itapiranga - SC. Initially through the theoretical foundation were discussed the main concepts of public policy and government agenda and its various stakeholders. Subsequently, a descriptive survey was conducted with a qualitative approach, survey through interviews with the surveyed municipalities. The description of the data shows that respondents view their municipal agendas as a key mechanism in the definition of ideas must prevail and integrate government plans. Denotes that the media has an influence on the various actors participating in the planning and implementation of agendas. It is inferred that the public agenda is influenced by immediate and sectorial demands. On the other hand, the agenda of government policy is influenced by several events as revenue frustrations, policy judicialization, electoral agenda, among others. The flow of the issues in the construction of government agenda has a little competition, its success is due to the strength of the actors and resource availability. The issues are influenced by their understanding as a problem and possible solutions, as well as, in some cases by political bargains. In conclusion, several actors such as the media, politicians, leaders, judiciary, counsel and government agents themselves are influential in developing the agendas process.